1995
DOI: 10.1073/pnas.92.19.8803
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Cw allele analysis by PCR-restriction fragment length polymorphism: study of known and additional alleles.

Abstract: We describe a technique for HLA-Cw genotyping by digestion of PCR-amplified genes with restriction endonucleases. Locus-specific primers selectively amplified HLA-Cw sequences from exon 2 in a single PCR that avoided coamplification of other classical and nonclassical class I genes. Amplified DNAs were digested with selected enzymes. Sixty-three homozygous cell lines from International Histocompatibility Workshop X and 113 unrelated individual cells were genotyped for HLA-Cw and compared with serology. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…Comparison of the data obtained in the present study with the DNA typing results for the Tenth IHW cell lines for HLA-C alleles (14,15) revealed that most HLA-C alleles except for Cw*0701, are shared by Japanese and Caucasians. On the other hand, comparison of the allele frequencies in the present Japanese population with those in a French population (6) showed that the predominant HLA-C alleles are different between these two populations. Cw*0102, 1403,0304,1202,0801 and Cw*0702 are the most frequent HLA-C alleles in the Japanese, while Cw*0702, Cw*0401, Cw*0501, and Cw*1601 are the most frequent in the French (Figure 2).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Comparison of the data obtained in the present study with the DNA typing results for the Tenth IHW cell lines for HLA-C alleles (14,15) revealed that most HLA-C alleles except for Cw*0701, are shared by Japanese and Caucasians. On the other hand, comparison of the allele frequencies in the present Japanese population with those in a French population (6) showed that the predominant HLA-C alleles are different between these two populations. Cw*0102, 1403,0304,1202,0801 and Cw*0702 are the most frequent HLA-C alleles in the Japanese, while Cw*0702, Cw*0401, Cw*0501, and Cw*1601 are the most frequent in the French (Figure 2).…”
Section: Discussioncontrasting
confidence: 51%
“…Cw*O401 is mainly associated with HLA-B62 in Japanese, and with B35 in Caucasians. Though both Cw*1402 and Cw*1502 were detected and found to be associated with HLA-B51 in Japanese and French, the predominant allele is Cw*1402 in Japanese and Cw*1502 in French (6).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously we developed the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method for HLA class I1 typing based on the digestion of PCR-amplified DNAs with allele specific enzymes which have a single recognition site in some alleles but none in other alleles in the aniplified regions (16). This PCR-RFLP method is easy and sensitive because genotypes can be simply defined by checking whether the amplified DNAs are digested or not, facilitating simple reading of the generated RFLP band patterns (17)(18)(19)(20)(21)(22). In the present study, we have first developed a DRB4 allele typing technique by PCR-RFLP and examined genomic polymorphism of the HLA-DRB4 gene DRB4*0101 : l l C AGG AAT CAG AAA GGA CAC TCT GGA ClT CAG CCA ACA GCA CTC l T G AGC TGA ~~~4 * 0 1 0 3…”
mentioning
confidence: 99%